Sustainability from farm to fork : education and the social construction of the environment in an agro-food park - the case of F.I.CO - Di Pumpo, Angela (SLU/Dept. of Urban and Rural Development, 2018)
Alternative food systems are emerging as a response to globalisation and industrialisation. With environmental destruction increasingly becoming an issue alongside with the growing concern about traditional food systems, unconventional trends in food sector have risen steeply in the past decades. Their birth has also been accompanied by the broadened target of environmental education, seeking to exit the formal classrooms and to embrace society with its various contexts. In the will to provide a creative answer to the unsustainability in food production and consumption, these emerging trends engage in representations and movements that generate problems of environmental justice and sustainability. This study investigates the problematization of environmental aspects within F.I.CO, a newly born agro-food park in Bologna.